In Vitro Examination of the VentriFlo True Pulse Pump for Failing Fontan Support. Issue 2 (4th November 2018) - Trusty, Phillip M.; Tree, Mike; Vincent, Doug; Naber, Jeffrey P.; Maher, Kevin; Yoganathan, Ajit P.; Deshpande, Shriprasad R.
Abstract: The current methodology of Fontan palliation results in a one "pump" circulatory system with passive flow to the lungs. Inherent hemodynamic differences exist between a biventricular circulatory system and this modified physiology, leading to a host of long‐term complications. Mechanical circulatory support (MCS) is a potential option to combat these pathophysiological conditions. In this study, we examine the VentriFlo True Pulse Pump as a MCS option to support a failing Fontan patient. An in vitro circulatory loop was used to model a failing Fontan patient, reproducing pathophysiological pressures and flow rates. The VentriFlo True Pulse Pump was positioned as a right sided support, testing multiple cannulation and baffle restriction strategies, as well as various pumping parameters including flow rate, frequency, stroke volume and the ejection to filling time ratio. A 10 mm Hg decrease in IVC pressure and 0.75 L/min increase in cardiac output were achieved using a complete baffle restriction strategy. Additional cannulation and banding strategies were not as successful. Pump flow rate and frequency significantly impacted hemodynamics, while the ejection to filling time ratio did not. Though not ideal, complete baffle restriction was necessary to achieve successful support. The ability to tune individual pumping parameters for a given MCS device will have a substantial impact on the pressures and flow augmentation seen in a Fontan circulation. Both future pump design and off‐label VADs for Fontan use should consider the pump configuration and parameter combinations presented here, which offered successful support.